A 24-Month Follow-Up Study of the Effect of Intra-Articular Injection of Autologous Microfragmented Fat Tissue on Proteoglycan Synthesis in Patients with Knee Osteoarthritis - Borić, Igor (Genes (Basel), 2019)
Osteoarthritis (OA) is a widely prevalent disease worldwide, and with an increasingly ageing society, it has become a challenge for the field of regenerative medicine. OA is a disease process involving multiple joint tissues, including those not visible on radiography, and is a complex disease process with multiple phenotypes that require evaluation by a multimodality imaging assessment. The purpose of this study was to evaluate the effect of micro-fragmented fat tissue intra-articular injection 24 months after application in two ways: Indirectly using functional magnetic resonance imaging (MRI) assessment analyzing the glycosaminoglycans (GAG) content in cartilage by means of delayed gadolinium (Gd)-enhanced magnetic resonance imaging of cartilage (dGEMRIC), as well as clinical outcome on observed level of GAG using standard orthopedic physical examination including VAS assessment. In our previous study assessing comprehensive results after 12 months, the dGEMRIC results have drawn attention. The present study explores the long-term effect of intra-articular injection of autologous microfragmented adipose tissue to host chondrocytes and cartilage proteoglycans in patients with knee OA. A prospective, non-randomized, interventional, single-center, open-label clinical trial was conducted from January 2016 to April 2018. A total of 17 patients were enrolled in the study, and 32 knees were assessed in a 12-month follow-up, but only 10 patients of them with 18 knees are included in a 24-month follow-up. The rest of the seven patients dropped out of the study 12 months after follow-up: three patients underwent knee arthroplasty, and the remaining four did not fulfil the basic criteria of 24 months involvement in the study. Surgical intervention (lipoaspiration), followed by tissue processing and intra-articular injection of the final microfragmented adipose tissue product into the affected knee(s), was performed in all patients. Patients were assessed for a visual analog scale (VAS), dGEMRIC at the baseline, three, six, 12 and 24 months after the treatment. A magnetic resonance sequence in dGEMRIC due to infiltration of the anionic, negatively-charged contrast gadopentetate dimeglumine (Gd-DTPA2) into the cartilage indicated that the contents of cartilage glycosaminoglycans significantly increased in specific areas of the treated knee joint. Our results suggest that this method of single intra-articular injection of autologous microfragmented adipose tissue improves GAG content on a significant scale, with over half of the measurements suggesting relevant improvement 24 months after intra-articular injection opposed to the expected GAG decrease over the natural course of the disease.